Comorbidities in Canadian patients with hereditary angioedema: a quantitative survey study - Paul K. Keith; Gina Lacuesta; Dawn Goodyear; Stephen D. Betschel; Belinda Yap; Marie-France Dansereau; Nataly Tanios; Rami El-Sayegh; Maye Machnouk; Hachem Mahfouz; Adriana Martin; Susan Waserman (Allergy, Asthma & Clinical Immunology)
Abstract Background Evidence linking hereditary angioedema (HAE) to the potential association of developing other comorbidities, and how it is affected by HAE treatment is needed. The objective of this study is to identify comorbidities and measure the prevalence in HAE patients, compared to the prevalence in the general population using multiple Canadian sources when available. Methods A quantitative survey design via a self-administered anonymous online questionnaire was conducted from October 13, 2022, to January 11, 2023. Respondents were individuals with HAE, enrolled in the CSL Behring patient support program (CSL Behring PLUS+; PSP). Results This study included 123 patients (81% female; 60% HAE-1/HAE-2, 24% HAE Normal C1-INH (nC1-INH), 16% unsure of HAE type; 85% of patients were on long-term prophylaxis plus on-demand). Patients reported using the following HAE treatments: C1-esterase inhibitor (subcutaneous or intravenous), lanadelumab, icatibant, danazol, and tranexamic acid. Respondents (69%) reported at least one: autoimmune condition, asthma, or allergy. Reported autoimmune conditions (psoriasis, rheumatoid arthritis, inflammatory bowel disease, chronic urticaria, lupus, and psoriatic arthritis) were much higher than the general population (31% versus 5–8%). Patient-reported allergies were two times higher than the general population (54% versus 27%; i.e., aeroallergens) and asthma rates nearly two times higher than the general population (17% versus 8–11%). Conclusion This cohort of HAE patients, most of whom were on prophylaxis, reported an increased prevalence of certain comorbidities compared to the general Canadian population. Healthcare professionals should be aware of the potentially increased risk of autoimmune conditions, allergies, and asthma in patients with HAE.